PENGARUH KONDISI SIMPAN DAN PERLAKUAN OSMOCONDITIONING TERHADAP VIABILITAS BENIH GMELINA (Gmelina arborea Roxb) - Syamsuddin Syamsuddin; Endang Murniati; Satriyas Ilyas; Endah Retno Palupi (Jurnal Agrista, 2003)
The research was conducted to study the effect of storage condition and osmoconditioning treatment on the viability of gmelina seed. The experiment was designed as a factorial experiment in a completely randomized design. The factors studied were storage condition (K), and osmoconditioning treatment (c). storage condition consist of room temperature condition (28-32oC) (K1) and under aircondition temperature (K2), where as osmoconditioning treatment consist of control (Co), PEG 0,4 MPa (C1), PEG 0,8 MPa (C2), KNO3 0,5 MPa (Ca3) and KNO3 0,1 MPa (C4). Observation was carried out in beweekly basis during sixteen weeks storage periods. The parameters observed were potential viability, growth strength vigour, and rate of metabolic activity changes. The research results showed the osmoconditioning treatment using PEG 0,4 and 0,8 MPa significantly increase total normal seedling. Moreover, osmoconditioning treatment using KNO3 0,5 MPa, and 1,0 MPa in the condition at under air conditioner room increase free fatty acid of the storage seed.